1987
DOI: 10.3109/08860228709047641
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance in Experimental Acute and Chronic Renal Failure in Rats

Abstract: Kidney cortical and medullary "spin-lattice" (T1) and "spin-spin" (T2) relaxation times were measured by spectroscopy in several types of experimental renal failure in rats. The T1 and the measured tissue water content were used to calculate the fraction bound (FB) and hydration fraction (HF) according to a fast proton diffusion model. The present study demonstrated the possibility to differentiate between normal and pathological renal tissue resulting from renal artery clamping (RAC), renal pedicle clamping (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…7 Imbalances in the water content between the cortex and the medulla were postulated as an explanation for the loss of the CMD on T1-weighted images of damaged kidneys. [7][8][9]11,12,[18][19][20][21][22][23] In addition to imbalances in the water content, decreased tubular fl ow or deposition of a variety of materials such as protein or blood in the medulla may result in increased signal intensity for the medulla on T1-weighted images. [9][10][11][12] For pairs of kidneys, the visual CMD on T1-weighted images provided almost perfect agreement with the renography results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Imbalances in the water content between the cortex and the medulla were postulated as an explanation for the loss of the CMD on T1-weighted images of damaged kidneys. [7][8][9]11,12,[18][19][20][21][22][23] In addition to imbalances in the water content, decreased tubular fl ow or deposition of a variety of materials such as protein or blood in the medulla may result in increased signal intensity for the medulla on T1-weighted images. [9][10][11][12] For pairs of kidneys, the visual CMD on T1-weighted images provided almost perfect agreement with the renography results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of clinical T 1 (and T 2 ) applications in the kidney can be found here [24]. The use of T 1 for noninvasive assessment of renal pathology in preclinical models has already been explored in the 1980s, showing that various effects including ischemia, tubular obstruction and renal congestion may attribute to T 1 differences in rat models of acute and chronic renal failure [25,26]. T 1 values can be affected by a wide variety of changes in the tissue environment, including inflammation and fibrosis.…”
Section: Overview Of Applications On Preclinical and Clinical Mr Instrumentsmentioning
confidence: 99%